Health risk assessment for adult loei residents exposed to arsenic in water and food around an abandoned gold mine - Hasan, MD Showket (Environmental and Toxicology Management, 2022)
This study assessed adult Loei residents’ health hazards of arsenic (As) exposure around an abandoned gold mine. Forty-five environmental samples were collected from 1, 5 and 10 km from the gold mine based on a survey of 371 random adults. Inductively Coupled Plasma Optical Emission Spectrometry determined total As in environmental samples following Thai regulatory limits. With that, a deductive approach was made to assess the health risks using United States Environmental Protection Agency (USEPA) guidelines. As concentrations above the guidelines were found in river water (0.05- 0.09 mg/L), highest in 10 km, and below the guidelines were throughout in public water (0.001-0.006 mg/L), freshwater fish, shrimp and mussels (0.12-.017, 0.15-0.58 and 0.26-0.33 mg/kg, respectively), and rice in 1 km (0.02 mg/kg) but no As in vegetables and fruits. Hazard quotients (HQs) and cancer risks (CRs) of water for daily and agricultural use, and CRs of shrimp and mussels all over were below the guidelines (HQ: 1, CR: 10-6 - 10-4), where HQs and CRs of rice and freshwater fish, and HQs of shrimp and mussels in 5 km (18.0-34.9 year olds) were above the guidelines. The inhabitants are at risk of developing non-cancerous and cancerous diseases via food consumption but through water.